Diode-pumped Nd:Gd3Ga5O12–KTiOPO4 green laser doubly passively Q-switched mode-locked by GaAs and Cr4+:YAG saturable absorbers. (2nd February 2015) - Qiao, Junpeng; Zhao, Jia; Yang, Kejian; Zhao, Shengzhi; Li, Yufei; Li, Guiqiu; Li, Dechun; Qiao, Wenchao; Li, Tao; Chu, Hongwei
Abstract: By simultaneously employing GaAs and Cr 4+ :YAG saturable absorbers, a diode-pumped doubly passively Q-switched and mode-locked (DP-QML) Nd:Gd3 Ga5 O12 (Nd:GGG)/KTiOPO4 (KTP) green laser has been presented. At the maximum incident pump power of 7.69 W, the obtained average output power, the pulse duration of the Q-switched envelope, the mode-locked pulse width and the pulse repetition rate are 62 mW, 16.8 ns, 352 ps, and 15.5 kHz, respectively, corresponding to a pulse energy of 4.2 µJ and a peak power of 0.25 kW. In comparison with singly passively Q-switched and mode-locked (SP-QML) green laser with GaAs or Cr 4+ :YAG saturable absorbers, the DP-QML green laser can generate shorter pulse width, deeper modulation depth and higher peak power. The coupled equations for diode-pumped doubly passively QML Nd:GGG/KTP green laser are given and the numerical simulations are in good agreement with the experimental results.